Efektivitas Intervensi Pendidikan Kesehatan Mengenai Manajemen Sindrom Premenstruasi dalam Meningkatkan Pengetahuan Remaja Putri - Yuhemy Zurizah; Rini Mayasari (STIKes Budi Mulia Sriwijaya, 2025)
Premenstrual Syndrome (PMS) is a collection of physical and emotional symptoms that appear before menstruation, such as breast tenderness, headaches, mood changes, and fatigue, which can interfere with the daily activities of adolescent girls (Fauziah et al., 2023). Globally, around 20–40% of individuals who menstruate experience PMS symptoms, with 2–8% experiencing a more severe form known as Premenstrual Dysphoric Disorder (PMDD). This study aims to evaluate the effectiveness of health education interventions on PMS management in improving the knowledge of adolescent girls in Palembang. This research is a quasi-experimental study without a control group, using a one-group pretest-posttest design. The study population consisted of the total population. The sample included 41 female students from grades VII and VIII at SMP Negeri 6 Talang Kelapa, Banyuasin Regency. The study was conducted in May 2025. Data analysis was performed using a paired T-test (dependent T-test) with the assistance of statistical software. The confidence level used was 95% with α = 0.05. Based on the results, the statistical test showed a p-value of 0.000 with a significance level of α = 0.05 (p < α), indicating a significant difference in the students' knowledge levels before and after the health education intervention. The conclusion of this study is that health education has a significant impact on increasing students' knowledge in managing Premenstrual Syndrome (PMS). This is evidenced by the increase in the average knowledge score from 7.04 before the intervention to 10.63 after the intervention, and a p-value of 0.000 (p < 0.05) indicating a significant difference. Before receiving health education, nearly half of the students did not understand how to manage PMS, but after the intervention, most students showed improved understanding.